'Sustainability of what, for whom? A critical analysis of Chinese development induced displacement and resettlement (DIDR) programs. (April 2022) - Xu, Hongzhang; Pittock, Jamie; Daniell, Katherine
Abstract: Most studies and influential agencies propose a shift to sustainability thinking and regard it as an important means of coordinating economic, social and environmental development. However, much less research focusses on conflicts over resources, the issue of asymmetrical power, and value-and-cultural conflicts behind the trajectories of sustainable development. For countries speeding up transitions such as China, it can be asked how and why might accelerating sustainability transitions through resettlement become a new utopia or a poverty trap? To examine the significance of this question for sustainability, we explore three development-induced displacement and resettlement (DIDR) programs in China: dam-induced resettlement, poverty-alleviation oriented relocation (including ecological migration) and agglomeration of villages. This research examines normative issues of Chinese policies for sustainability. We find that building sustainability via DIDR will not be as easy as projected and could lead to new poverty traps that disadvantage some groups of people, such as resettlees. We highlight three themes, the change of resettlees' financial conditions, land access and local governance, to explore how competition is skewed between resettlees and local governments while speeding up to pursue more ambitious goals. We find that with the increased pace of implementation of quick sustainability policies that power lies with local governments to the detriment of resettlees. DIDR can become a just governance tool to build sustainability, but only if there is sufficient agreement among all stakeholders on a transparent, accountable and collaborative approach. Without inclusion and equality in transitions, potential risks and challenges can eclipse sustainable development. Graphical Abstract: ga1 Highlights: Adopting resettlement to accelerate sustainability transitions is again in policy agenda of many countries and regions to advance social goals and modernity. Resettlement can break up hierarchical social structures and could benefit previously disadvantaged people, such as women and the disabled. In China, the increased pace of implementation of quick sustainability policies that power lies with local governments to the detriment of resettlees. Building sustainability often requires trade-offs rather than win-win solutions.